The relationship between serum interleukin-10 (IL-10) and preeclampsia in pregnant women in the third trimester in Bandar Abbas - Khazaei-Koohpar M; Azin-Alavi (Fiyz̤, 2020)
Background: Preeclampsia is one of the important factors in maternal and fetal mortality and it seems that changes in immunological factors such as auto antibodies and the presence of various cytokines contribute to the disease. This study aimed to determine the relationship between serum Interleukin-10 (IL-10) levels in pregnant women and preeclampsia during the third trimester of pregnancy in Bandar Abbas, southern Iran. Materials and Methods: In this case-control study, 60 pregnant women were examined in two groups of case and control. All mothers were in the third trimester of pregnancy. Sixty pregnant women were included in the study, of which 30 women had preeclampsia (case group) and 30 women had normal blood pressure (control group). After selecting the subjects, 5cc blood samples were collected from the case group and control group. Then, the level of IL-10 was measured in the serum sample. Data were analyzed by t-student and Mann-Whitney tests. Results: The mean IL-10 level among the mothers in the case group was 22.25 and it was 38.75 in the control group. IL-10 was significantly lower among mothers in the case group (P<0.001). The statistical analysis in this study demonstrated that if IL-10 is increased by one unit, the risk of preeclampsia decreases by 1.36 times (P=0.001). Conclusion: Considering the results of this study, it seems that serum levels of IL-10 play a significant role in the incidence of preeclampsia among pregnant mothers. These findings can be used for diagnostic and therapeutic purposes.